Sources, Status, and Potential Risks of Microplastics in Marine Organisms of the Bohai Sea: A Systematic Review - Jian Yang; Hongxia Li; Wei Ling; Yifei Li; Kangkang Zhang; Pu Zhang (Toxics)
This study focused on microplastic pollution in the Bohai Sea, employing bibliometric analysis and meta-integration methods to systematically analyze its pollution characteristics and ecological risks. The results indicated that microplastics primarily originated from land-based inputs (62%) and marine activities (23%). Microplastic concentrations in the Bohai Sea’s coastal areas were significantly higher than in deep waters, and the abundance of microplastics in aquaculture sediments was three to five times that in non-aquaculture areas. Bioaccumulation demonstrated a significant trophic magnification effect, with top predators containing much higher microplastic concentrations than plankton. The combined toxicity of microplastics and pollutants severely impacted key species, leading to a 92% decrease in Chinese shrimp populations and a significant reduction in benthic biodiversity. To address this issue, a “four-in-one” prevention and control system was proposed, encompassing source reduction, intelligent monitoring, targeted treatment, and regional collaboration, with measures including policy, technological innovation, and ecological restoration. This aims to provide scientific evidence for Bohai Sea ecological security management and offer a reference for microplastic management in globally semi-enclosed seas.